The implications of management practices on life cycle greenhouse gas emissions in biogas production - Lehtoranta, Suvi; Tampio, Elina; Rasi, Saija; Laakso, Johanna; Vikki, Karetta; Luostarinen, Sari (Academic Press, 2024)
Biogas production is seen as one of the key measures in circular economy providing several benefits for the environment. In practice, however, these benefits may not be achieved if the production is not implemented and managed in ways that reduce gaseous emissions. Thus, this study aimed at highlighting how different management practices impact the climate during the life cycle of biogas production in comparison to management without biogas production (reference). Advanced, more emission-reducing practices resulted in 97–107% and conventional practices in 57–75% less emissions when biogas was utilized as transport fuel. If biogas was utilized in CHP (combined heat and power production), the emission reductions were 67–74% and 13–30%, respectively. This reflects the fact that inefficient practices can lead to minimal emission reduction without achieving the desired climate benefit in comparison to the reference. On the European level, this may also mean that the emission reduction demands of RED II (Renewable Energy Directive) regulation are not met. Therefore, when supporting biogas production with public funds, assurance of using emission-reducing practices should be made a prerequisite.
Keywords: biogas; sustainability; methane; emissions; LCA; REDII